Beyond the spine: a case of ankylosing spondylitis complicated by secondary amyloidosis - Anjlee Sawlani; Rida Masood (Egyptian Rheumatology and Rehabilitation, 2024)
Abstract Background Ankylosing spondylitis (AS) is a chronic inflammatory condition primarily affecting the spine and sacroiliac joints, often associated with human leukocyte antigen B27 (HLA-B27) positivity. While musculoskeletal symptoms are typical manifestations, AS can also lead to systemic complications, including secondary systemic amyloidosis (SSA), also known as Amyloid A (AA) amyloidosis, involving multiple organs. Case presentation We present a case of a 45-year-old Asian male with a complex medical history, including diabetes and hypertension, who developed AS complicated by SSA. The patient exhibited a diverse range of symptoms, including cardiac, renal, gastrointestinal, and musculoskeletal manifestations. He reported shortness of breath on exertion, orthopnea, pedal edema, generalized weakness, back pain, neck pain, low-grade fever, decreased appetite, frothy urine, and significant weight loss over the past year. Diagnostic evaluations revealed HLA-B27 positivity and histologically confirmed AA amyloidosis, providing a comprehensive understanding of the systemic involvement. Conclusion This case report highlights the intricate interplay between AS and SSA, particularly AA amyloidosis, with a focus on its systemic impact beyond musculoskeletal symptoms. The tragic outcome, marked by severe cardiac involvement, underscores the challenges in managing such complex cases. This report emphasizes the importance of early diagnosis and treatment of AS to prevent severe complications, along with vigilant monitoring and individualized treatment plans, as well as the need for further research to enhance our understanding and improve management strategies for AS-related amyloidosis.